2013
DOI: 10.1002/hc.21077
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry. Reaction of Elemental Phosphorus (P4) and Elemental Sulfur with Protonodonor Reagents: New Methods for the Synthesis of Ammonium Salts of S,S′‐Dialkyltetrathiophosphoric Acids and Octathiotetraphosphetane

Abstract: A new reaction of white phosphorus (P4) with elemental sulfur and thiols in the presence of different amines has been investigated. Ammonium salts of S,S′‐dialkyltetrathiophosphoric acids have been observed as main products of the reaction. Octathiotetraphosphetane ammonium salts were formed as side products. The reaction is characterized by a complete conversion of the white phosphorus and is not accompanied by the release of hydrogen sulfide. The crystal structures of both products were determined by the sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The biological activity of tetraphosphetane derivatives ( 1 , 2 ) and their metal complexes ( 3–9 ) was the next subject of our investigations. Compounds were tested against Gram‐positive ( Staphylococcus aureus , Streptococcus pyogenes ) and Gram‐negative ( Acinetobacter baumannii , Pseudomonas aeruginosa ) bacteria and did not show any definitive antibacterial properties . However, transition metal complexes of octathiotetraphosphetane do show some antifungal and anticancer activity.…”
Section: Resultsmentioning
confidence: 99%
“…The biological activity of tetraphosphetane derivatives ( 1 , 2 ) and their metal complexes ( 3–9 ) was the next subject of our investigations. Compounds were tested against Gram‐positive ( Staphylococcus aureus , Streptococcus pyogenes ) and Gram‐negative ( Acinetobacter baumannii , Pseudomonas aeruginosa ) bacteria and did not show any definitive antibacterial properties . However, transition metal complexes of octathiotetraphosphetane do show some antifungal and anticancer activity.…”
Section: Resultsmentioning
confidence: 99%
“…When thiols were added to the reaction, the main products were ammonium salts of S , S′ ‐dialkyltetrathiophosphoric acids (Scheme ) …”
Section: Sulfur As Building Block – Sulfuration Reactionsmentioning
confidence: 99%
“…We have demonstrated that the reactions of elemental (white) phosphorus (P 4 ) and sulfur (S 8 ) in the presence proton donors (alcohols, phenols) and various amines proceed easily and yield ammonium salts of O,O'-diesters of dithiophosphoric acid. 1–3 More recently we have shown 4 that the use of aliphatic thiols as proton donors in the reaction of elemental (white) phosphorus with sulfur and amines led to the synthesis of two phosphorus-containing products. Ammonium salts of S,S'-dialkyltetratiophosphoric acid were the main products while the four-membered cyclic phosphorus derivatives - ammonium salts of octathiotetraphosphetane were the minor products (yield 18–20%) in this reaction.…”
Section: Introductionmentioning
confidence: 99%